2017
DOI: 10.1139/cjps-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

A MADS-box gene associated with protocorm-like body formation in Rosa canina alters floral organ development in Arabidopsis

Abstract: We isolated a gene encoding a putative MADS-box protein designated RcAGL15 from PLB (Protocorm-like body, a somatic embryogenetic structure) of Rosa canina. RcAGL15 encodes a predicted protein of 251 amino acid residues with a molecular weight of 28 kDa and theoretical isoelectric point of 7.5. RT-PCR shows that RcAGL15 is mainly expressed in PLB and regenerated PLB, but not in leaves of aseptic seedlings, incubated leaflets before callus formation, calli, rhizoids or leaves of regenerated shoots. Transgenic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…To circumvent such limitations in the meantime, some rose genes have been studied in heterologous systems, including Tobacco 131 , Pelargonium 132 and Arabidopsis 85,133135 . Systems for transient expression in rose have been developed by agroinfiltration in petals (e.g.…”
Section: Speeding Up Functional Gene Identificationmentioning
confidence: 99%
“…To circumvent such limitations in the meantime, some rose genes have been studied in heterologous systems, including Tobacco 131 , Pelargonium 132 and Arabidopsis 85,133135 . Systems for transient expression in rose have been developed by agroinfiltration in petals (e.g.…”
Section: Speeding Up Functional Gene Identificationmentioning
confidence: 99%
“…For example, plant transformation in soybean is accelerated when overexpression of AGL15 enhances somatic embryogenesis, which could be utilized for producing elite cultivars. Similarly, AGL15 could provide a vital role in scaling up production of valuable crops such as coffee through propagation and genetic transformation (Etienne et al, 2018 ; Xu et al, 2018 ). Other crops could benefit from examining AGL15 expression in their species, and possibly enhancing transformation strategies via better regeneration by SE.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The non-embryogenic line (A17) showed no such increase. Ghadirzadeh-Khorzoghi et al ( 2019 ) showed increased PvAGL15 transcript in embryogenic explants of pistachio, while Xu et al ( 2018 ) showed RcAGL15 associated with protocorm-like bodies in rose.…”
Section: Systems Where Agl15 Has Been Found To Promote Somatic Embryo...mentioning
confidence: 99%
“…In addition to controlling floral transition, ectopic expression of AtAGL15 or AtAGL18 in Arabidopsis can also enhance somatic embryogenesis, affect leaf morphogenesis, reduce fertility, and delay floral organ senescence and abscission [14,16,17], indicating the redundant functions of AtAGL15 and AtAGL18 in these developmental processes. AtAGL15 orthologs have been functionally characterized in other plants, such as cotton (G. hirsutum) [18], soybean (Glycine max) [19][20][21], Rosa canina [22], and Brassica juncea [23]. In addition, AGL15 members can control diverse developmental processes by modulating the hormone signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For example, AtAGL15 and GmAGL15 negatively regulate auxin signaling pathway to promote somatic embryogenesis in Arabidopsis and soybean, and this regulation is integrated with GA metabolism and ethylene signaling pathway [19,20,24,25]. Overexpression of an AtAGL15 ortholog from R. canina in Arabidopsis altered floral organ morphology and numbers, as well as somatic embryogenesis, with a reduction in IAA and GA contents [22].…”
Section: Introductionmentioning
confidence: 99%